Photonics-aided broadband terahertz communication technology - Jianjun YU; Wen ZHOU; Xinyi WANG; Kaihui WANG (Tongxin xuebao, 2022)
Firstly, the key technologies in photonics-aided broadband terahertz communication systems were introduced, and then the research progress in large-capacity and long-distance terahertz communication technologies was introduced.Using these key technologies, wireless transmission of THz signals had been successively achieved exceeding 1 Tbit/s, wireless transmission of THz signals exceeding 100 Gb/s for 54.6 meters without a THz amplifier.The use of air-core optical fiber to transmit terahertz signals exceeding 100 Gbit/s was also introduced.